Constructing optimized Boolean functions - CHEN Wei1; YANG Yi-xian1; NIU Xin-xin2 (Tongxin xuebao)
Considering connections of characteristics,aiming construction for the optimized Boolean functions,new method based on Bent function,discrete Walsh spectrum and characteristics matrices were presented by concatenating,breaking,and revising output sequence conditionally.This new construction can be used to construct kinds of functions satisfying different design criteria as deeds.